Nationalism, Democratisation and Primordial Sentiment in Indonesia: Problems of Ethnicity versus Indonesian-ness (the cases of Aceh, Riau, Papua and Bali) - Gayatri, Irine Hiraswari (RMPI-BRIN, 2010)
-